Pengaruh Mekanisme Corporate Governance, Leverage, dan Free Cash Flow terhadap Manajemen Laba Akrual(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di LQ45 Periode 2010-2015) - Mardayaningrum, Mardayaningrum; , Dra. RinaTrisnawati, MSi, Akt. Ph.D (2017)
This purpose of this study is to examine and analyze the mechanisms of corporate governance, leverage and the free cash flow against the management profit (empirical studies on the effect of buersa in LQ45 index indonesia (idx) tahn 2010-2015). The number of samples in the study originally 160 companies, because it is not distributed normal then performed an outlier on the sample final sample then be 144 companies. Sampling techniques using a purposive sampling method. Analysis on the research using SPSS program. Methods of analysis using multiple linear regression to test and prove the hypothesis of the study. Research results showed the corporate governance mechanism with institutional ownership, managerial ownership, the proportion of Board of Commissioners and the audit committee no effect significantly to earnings management. It is seen from the value t calculate > t tables and probability > 0.05. While free cash flow and leverage significantly to earnings management. It is seen from the value t calculate > t tables and probability < 0.05. Keywords:corpotare governace, leverage, free cash flow, earnings manajemen